1994
DOI: 10.1007/bf00004114
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of seawater acclimation in the striped bass, Morone saxatilis (Walbaum)

Abstract: Several experiments were performed to investigate the physiology of seawater acclimation in the striped bass, Morone saxatilis. Transfer of fish from fresh water (FW) to seawater (SW; 31-32 ppt) induced only a minimal disturbance of osmotic homeostasis. Ambient salinity did not affect plasma thyroxine, but plasma cortisol remained elevated for 24h after SW transfer. Gill and opercular membrane chloride cell density and Na(+),K(+)-ATPase activity were relatively high and unaffected by salinity. Average chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 40 publications
4
32
2
Order By: Relevance
“…Strong antigen recognition with the anti-CFTR antibody was observed in the same positions in the filament section where Na C ,K C -ATPase immunoreactivity occurred, suggesting that these two proteins are located within the same type of cells, presumably chloride cells. Except for faint staining of lamellar pavement cells, immunocytochemistry using the CFTR antibody confirms that there are virtually no lamellar chloride cells in either FWor SW-striped bass (Madsen et al 1994). The similar CFTR staining pattern and intensity in FW and SW gills is very different from the situation in killifish , Hawaiian goby , eel (Anguilla anguilla; Wilson et al 2004) and tilapia (Hiroi et al 2005), where both pattern and intensity of staining change significantly in response to salinity shifts.…”
Section: Cftr and Salinity Changementioning
confidence: 80%
See 4 more Smart Citations
“…Strong antigen recognition with the anti-CFTR antibody was observed in the same positions in the filament section where Na C ,K C -ATPase immunoreactivity occurred, suggesting that these two proteins are located within the same type of cells, presumably chloride cells. Except for faint staining of lamellar pavement cells, immunocytochemistry using the CFTR antibody confirms that there are virtually no lamellar chloride cells in either FWor SW-striped bass (Madsen et al 1994). The similar CFTR staining pattern and intensity in FW and SW gills is very different from the situation in killifish , Hawaiian goby , eel (Anguilla anguilla; Wilson et al 2004) and tilapia (Hiroi et al 2005), where both pattern and intensity of staining change significantly in response to salinity shifts.…”
Section: Cftr and Salinity Changementioning
confidence: 80%
“…Previous studies have shown a well-developed ability of striped bass to acclimate to salinities ranging from FW to fullstrength SW. Madsen et al (1994) and Tipsmark et al (2004) reported very small and short lasting (!24 h) deflections of ion-osmotic homeostasis, when fish were transferred between FW and SW in either direction. They concluded that rapid, post-transcriptional regulation of ion-transport function was responsible for this ability.…”
Section: Cftr and Salinity Changementioning
confidence: 95%
See 3 more Smart Citations